2019
DOI: 10.21815/jde.019.032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effectiveness of Two Teaching Methods on Acquisition of Skills in Preclinical Fixed Prosthodontics

Abstract: The aim of this study was to evaluate the effects of dental faculty‐student interactions, virtual assessment software, and associated rubrics on student performance by assessing tooth preparations generated during the students' final practical exam. The study, conducted in 2017 and 2018, compared teeth prepared for preclinical fixed prosthodontics competency exams by two subsequent classes of second‐year dental students trained using different methods. Class A was trained for nine months prior to the exam usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Additionally, some studies have reported usefulness of the digital educational device from standpoints of objective assessment. 8 , 9 , 10 , 11 , 12 , 13 Thus, the digital simulator would hold the promise of its great potential in dental education, however, it has not yet been widespread in dental schools in the world. 1 Majority is still the conventional simulator training, in which trainees cut artificial teeth attached on phantom head and teachers perform visual inspection to make assessment and instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some studies have reported usefulness of the digital educational device from standpoints of objective assessment. 8 , 9 , 10 , 11 , 12 , 13 Thus, the digital simulator would hold the promise of its great potential in dental education, however, it has not yet been widespread in dental schools in the world. 1 Majority is still the conventional simulator training, in which trainees cut artificial teeth attached on phantom head and teachers perform visual inspection to make assessment and instruction.…”
Section: Introductionmentioning
confidence: 99%
“…This high approval rating might be due not only to the immediacy of the visual feedback, but also to the generally enthusiastic attitude of dental students towards digital dentistry [ 53 ]. Commercial digital evaluation systems, such as PrepCheck ® (Dentsply Sirona©, Bensheim, Germany), Dental Teacher™ (KaVo©, Biberach, Germany) and Compare© (Planmeca©, Helsinki, Finland), that report feedback on students’ prosthetic preparations through a comparison with reference preparation scans are already available [ 54 , 55 , 56 ]. To the best of our knowledge, only one other study used IOS as a learning tool for students in endodontic preclinical training.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches to acquisition of procedural skills call on assessment after the procedure is completed rather than assessing the student's ability to conceptualize the procedural outcome before beginning. 27,28 Clinical textbooks show extensive patient treatments, 29,30 but specifics on conceptualizing the procedural outcome and the path to that outcome are minimal. A remaining question is the extent to which the student's grasp of the procedural outcome improves their performance on reaching that outcome.…”
Section: Procedural Outcome Conceptualized To Procedures Completedmentioning
confidence: 99%